Estimation of capacitors stray inductance by the analysis of overdamped discharge current curves - Kostiukov, Ivan Oleksandrovich (Товариство польських інженерів електротехніки та електроніки, 2021)
This paper gives a description of measurement method which can be used in practice of carrying out measurement of stray inductance of tested capacitive object with the unknown value of electrical capacitance. Stray inductance is determined by means of analysis of previously smoothed by the least squares method curves of discharge current caused by overdamped discharge of tested capacitive object. An example of practical implementation and the analysis of factors that affect the accuracy of proposed method are also given.

W artykule opisano metodę pomiarową, która może być zastosowana w praktyce do pomiaru indukcyjności rozproszonej badanego obiektu pojemnościowego przy nieznanej wartości pojemności. Indukcyjność rozproszoną wyznacza się na podstawie analizy wygładzonych wcześniej metodą najmniejszych kwadratów krzywych prądu wyładowania wywołanego rozładowaniem badanego obiektu pojemnościowego. (Oszacowanie indukcyjności rozproszonej kondensatorów na podstawie analizy prądów rozładowania).
Keywords: correlation coefficient; dielectric permittivity; insulation testing; voltage drop; indukcyjność roz[proszona; kondensator; prąd rozładowania; коефіцієнт кореляції; діелектрична проникність; випробування ізоляції; падіння напруги